2018
DOI: 10.1002/htj.21407
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study on heat transfer and flow characteristics in an alternating cross‐section flattened tube

Abstract: An experimental and numerical study on convection heat transfer of water flowing through an alternating cross-section flattened (ACF) tube are investigated in this paper. The thermal-fluid characteristics were evaluated by numerical simulation. The test run conditions covered a mass flux of 200 to 800 kg m −2 s −1 , a heat flux of 10 kW/m 2 , and an inlettemperature of 40°C. The results showed that the Nusselt number increased with the increase in mass flux. Moreover, the heat transfer was also affected by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Rukruang et al [27] studied the heat transfer coefficient (HTC) and pressure drop of water flowing through a 90° alternating cross-section flattened (ACF) tube compared with a circular tube. The result showed that the HTC and flow resistance of the ACF tube were higher, and the thermal performance was 3.4 times better.…”
Section: Introductionmentioning
confidence: 99%
“…Rukruang et al [27] studied the heat transfer coefficient (HTC) and pressure drop of water flowing through a 90° alternating cross-section flattened (ACF) tube compared with a circular tube. The result showed that the HTC and flow resistance of the ACF tube were higher, and the thermal performance was 3.4 times better.…”
Section: Introductionmentioning
confidence: 99%
“…Helical tube heat exchangers are used in compact heat exchangers like evaporators, condensers, food industry, power stations, and air conditioners. Based on this, numerous experimental and numerical studies have thoroughly analyzed the enhancement of heat transfer in heat exchangers 1–7 . Among them, helical tubes have attracted much attention due to their high thermal performance 8–16 .…”
Section: Introductionmentioning
confidence: 99%